2009
DOI: 10.1016/j.bbrc.2009.03.080
|View full text |Cite
|
Sign up to set email alerts
|

An anti-apoptotic peptide improves survival in lethal total body irradiation

Abstract: Cell penetrating peptides (CPPs) have been used to deliver the anti-apoptotic Bcl-xL-derived BH4 peptide to prevent injury-induced apoptosis both in vitro and in vivo. Here we demonstrate that the nuclear localization sequence (NLS) from the SV40 large T antigen has favorable properties for BH4 domain delivery to lymphocytes compared to sequences based on the HIV-1 TAT sequence. While both TAT-BH4 and NLS-BH4 protected primary human mononuclear cells from radiation-induced apoptotic cell death, TAT-BH4 caused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…The most N-terminal BH region, the BH4 domain, distinguishes these antiapoptotic proteins from some, but not all, of their proapoptotic counterparts [4,5]. Interestingly, recent studies revealed that the BH4 helix, either as isolated peptide [6][7][8][9][10], or as an integral part of full-length Bcl-2 [11][12][13][14][15][16] possesses an antiapoptotic activity separated from or additive to the one mediated by the other three BH domains (BH1-3). At the mitochondria, the BH4 domain of Bcl-2 prevents BAX activation [9].…”
Section: Introductionmentioning
confidence: 99%
“…The most N-terminal BH region, the BH4 domain, distinguishes these antiapoptotic proteins from some, but not all, of their proapoptotic counterparts [4,5]. Interestingly, recent studies revealed that the BH4 helix, either as isolated peptide [6][7][8][9][10], or as an integral part of full-length Bcl-2 [11][12][13][14][15][16] possesses an antiapoptotic activity separated from or additive to the one mediated by the other three BH domains (BH1-3). At the mitochondria, the BH4 domain of Bcl-2 prevents BAX activation [9].…”
Section: Introductionmentioning
confidence: 99%
“…Recent growing evidence suggests that such irradiation can influence immune system function (Gridley et al 2006;Hayashi et al 2005;McDunn et al 2009). It is subsequently important to investigate the effect of heavy ions on peripheral blood lymphocytes (PBL), a major component of the human immune system.…”
Section: Introductionmentioning
confidence: 99%
“…Bcl-x L is a Bcl-x splicing variant and has anti-apoptotic ability [ 18 ]. Indeed, Bcl-x L overexpression reduces gamma irradiation–induced apoptosis, and BH4 peptides derived from Bcl-x L have been demonstrated to protect mice from death due to high-dose radiation [ 19 , 20 ]. Because BH4 forms part of the N-terminal of Bcl-x L , and because the antibody used in the present study recognizes 3–14 amino acids of Bcl-x L , these findings suggest that high and acute irradiation suppresses Bcl-x L expression, indicating the promotion of radiation damage, that is, apoptosis induction.…”
Section: Discussionmentioning
confidence: 99%